2007
DOI: 10.1021/bc7002082
|View full text |Cite
|
Sign up to set email alerts
|

Gene Delivery Properties of End-Modified Poly(β-amino ester)s

Abstract: Here, we present the synthesis of a library of end-modified poly(beta-amino ester)s and assess their utility as gene delivery vehicles. Polymers were synthesized using a rapid, two-step approach that involves initial preparation of an acrylate-terminated polymer followed by a postpolymerization amine-capping step to generate end-functionalized polymers. Using a highly efficient poly(beta-amino ester), C32, we show that the terminal amine can greatly affect and improve polymer properties relevant to gene delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
(82 reference statements)
3
75
0
Order By: Relevance
“…S1) (7)(8)(9)(10)(11)(12)(13). PBAE polymers were synthesized by a two-step Michael addition, as previously reported (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…S1) (7)(8)(9)(10)(11)(12)(13). PBAE polymers were synthesized by a two-step Michael addition, as previously reported (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, monomers 1 and 7 contain two amine groups, whereas monomers 9 and 11 contain two alcohol groups. Both functionalities have been previously associated with increased gene delivery (25,26,29).…”
Section: Significancementioning
confidence: 97%
“…To improve upon delivery specificity, mannose, an antagonist of CD206 (primarily expressed on APCs) (35,36), was grafted onto D9 (8,29,37,38). In addition to promoting APC delivery specificity, CD206 is a type 1 membrane immune receptor that mediates uptake of bacteria (39).…”
Section: Significancementioning
confidence: 99%
“…Lead polymer C32 was end-capped with an expanded library of 36 different amines by Zugates et al to show wider structure/function relationships ( Figure 9C). 36,37 Lead modified polymers C32-103 and C32-117 were found to bind DNA with higher affinity and form nanoparticles that were ~30% smaller than those formed with regular amino alcohol terminated C32. 35 We also found that these modified PBAE nanoparticles enable an up to 5-fold increase in cellular DNA uptake compared with regular C32.…”
mentioning
confidence: 99%